Major Factors Influencing the Utilization of Maternal Health Services in Nepal - Alessi, Kaitlyn; Ierardi1, Michael; Anderson, Nadia; Blavo, Cyril; Marahatta, Sujan Babu (Journal of Karnali Academy of Health Sciences, 2023)
Background: According to the World Health Organization, maternal health services (MHS) include antenatal care, perinatal care, and postnatal care. MHS have been underutilized in Nepal and are contributing to an increased morbidity and mortality in the region leading to various adverse outcomes for both mothers and their newborns. Many of these adverse outcomes can be avoided with increased use of antenatal, perinatal, and postnatal checkups.Methods: Literature reviews of existing information about MHS in Nepal presents an opportunity to identify the source of underutilization and by understanding the source, plans can be proposed to improve MHS. Search for the data was achieved through Medline, Springerlink, and Nepal journals online; with additional articles found by branching off the references of those articles. Publications were limited to those written or translated into English, and those related to Nepal demography. Articles were excluded if the report was not referring specifically to Nepal. In this study, all three natal periods are addressed.Results: Cultural aspects, educational aspects and accessibility have been determined to be the leading causes of the underutilization of MHS.Conclusion: Using this new understanding, interventions focused on improving and providing education about these barriers should lead to reduced morbidity and mortality among mothers and their newborns in Nepal.